Immuno-isolation of highly purified peroxisomes using magnetic beads and continuous immunomagnetic sorting - Lüers, Georg H.; Hartig, Roland; Mohr, Heribert; Hausmann, Michael; Fahimi, H. Dariush; Cremer, Christoph; Völkl, Alfred (Electrophoresis, 1998)
Immuno-isolation is a powerful technique for the isolation of cells as well as subcellular organelle populations based on their antigenic properties. We have established a method for immuno-isolation of peroxisomes (PO) from both rat liver and the human hepatoblastoma cell line HepG2 using magnetic beads as solid support. A polyclonal antibody raised against the cytoplasmic C-terminal 10 amino acids of the rat 70 kDa peroxisomal membrane protein was covalently bound to magnetic beads (Dynabeads M-450). The coated beads were incubated with a light mitochondrial fraction and the organelle-bead complexes formed were separated by magnetic sorting in a free-flow system without pelleting the complexes during the isolation procedure. Scanning electron microscopy revealed decoration of beads with particles measuring 150-400 nm in diameter. The particles were identified as PO by catalase cytochemistry and biochemically by marker enzyme analysis, sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) as well as immunoblotting for specific detection of peroxisomal matrix, core and membrane proteins. The functional significance of PO in man is emphasized by the existence of inherited diseases such as the Zellweger syndrome in which intact PO are lacking, but peroxisomal remnants called “ghosts” are observed instead. Peroxisomal disorders are usually studied using skin fibroblast cell lines derived from afflicted patients and immuno-magnetic separation may prove particularly useful for the investigation of such cultured cells and for further elucidation of the pathogenesis of fatal peroxisomal disorders.